[Suds story ; Bote garapa ; Hari ng Stunt [videorecording] - Lazaro, Cheche (The Probe Team, 1991)
Investigates the hard detergent bar as polluting the environment. Patis, toyo, bagoong are staples that come bottled in recycled gun bottles. A House bill proposes that the practice be stopped. The staple manufacturers say that recycling is well within their rights. The gin makers are up in arms against what they call a usurpation of their property rights. Features stuntmen in the movies.